Сущность и место рефлексии в управленческой деятельности - Высочина, М.В.; Сейдаметова, А.А. (Культура народов Причерноморья, 2014)
Управленческое решение является результатом мыслительной работы и неразрывно
связано с рефлексией. Основное содержание исследования составляет анализ сущности понятия
рефлексия с точки зрения различных сфер её изучения и определение места рефлексии в управленческой
деятельности. В статье сформулированы специфические особенности управленческой деятельности и
управленческого решения как результата (продукта) этой деятельности. Уточнено определение
рефлексии. Определено место рефлексии в процессе принятия управленческих решений. Управлінське рішення є результатом розумової роботи й нерозривно пов'язане з рефлексією.
Основний зміст дослідження становить аналіз сутності поняття рефлексія з точки зору різних сфер її
вивчення та визначення місця рефлексії в управлінській діяльності. У статті сформульовані специфічні
особливості управлінської діяльності та управлінського рішення як результату (продукту) цієї
діяльност. Уточнено визначення поняття «рефлексія». Визначено місце рефлексії в процесі ухвалення
управлінських рішень. This work has an interdisciplinary nature, written at the junction of sciences such as philosophy,
psychology, sociology, pedagogy and management. The main content of the study is the analysis of the essence
of the concept of reflection in terms of various fields of study and its definition of a place of reflection in а
managerial work. It should be noted that the issue is not enough studied today and needs more study.
Reflection has three main functions (research, critic and valuate) and has a particular impact on the
effectiveness of managerial work. Manager should own the means of mental work (concepts and categories) to
be able to compare the theoretical concepts with observations of actual practice activities, identify differences based on the identified discrepancies to make responsible decisions. It is impossible to develop the ability to
anticipate people's reactions to the upcoming events without an analysis of his own actions, as well as the
analysis of people's reactions to these actions. This ability becomes the driving force for the development of
effective, more correct and precise work strategy and development of the company, plays an important role in
the formation of stable, cohesive team through the use of a specific approach to each employee.
The article defines the specific features of managerial work and administrative decision as a result of (product)
of this work. A new definition of reflection is proposed. The place of reflection in decision-making is identified.